Paramagnetic NMR analysis of substituted biscyclooctatetraene lanthanide complexes - Hiller, Markus; Maier, Martin V.; Wadepohl, Hubert; Enders, Markus (Organometallics, 2016)
Cyclooctatetraene derivatives (COTR) with two carbocycles attached to the central ring have been used as dianionic ligands for the synthesis of double-decker complexes of the type [(COTR)2M]−. Two ligand derivatives were combined with diamagnetic Y3+ and with the five paramagnetic lanthanide ions from Tb3+ to Tm3+. The more complex substitution pattern in comparison to the parent ligand COT or the popular bis-trimethylsilyl derivative allows a sufficient number of signals to be obtained for a comprehensive paramagnetic NMR analysis. The anionic double-decker complexes gave well-resolved NMR spectra where almost all 1H and 13C NMR signals could be detected and assigned. With these data, it was possible to separate the two main contributions to the paramagnetic shift (pseudocontact and Fermi contact shifts, respectively) and to determine the magnetic anisotropy of the lanthanide ions in their ligand fields. We can easily obtain the sign and the magnitude of the anisotropy of the magnetic susceptibility, which is itself strongly related to the energy barrier for spin reversal in single-molecule magnets. Our results confirm that Bleaney factors are inadequate descriptors for magnetic anisotropy in these lanthanide complexes.